Parental care of Elaenia albiceps nestlings in the Andean-Patagonian Forest - Gorosito, Cristian Andrés (2017)
Most bird species provide biparental care, which is mainly observed in monogamous species with altricial nestlings. Biparental care is not always equally shared between sexes, and females provide more parental care than males. Our aim was study the parental care in Elaenia albiceps, which is a migrant species that reproduces in the Andean-Patagonian Forest during the austral summer. Field work took place in Esquel, Argentina, in two breeding seasons (2015/2016 and 2016/2017). E. albiceps nests were filmed during 45-90 minutes when the nestlings were 2-4 days and 9-10 days old (they were close to becoming fledglings). The provisioning frequency of nestlings by females was higher than the one for males, and both sexes increased their provisioning frequencies with the age of nestlings. Those females that fed nestlings alone had the same provisioning frequency than the females assisted by males. We differentiated males that did not provide parental care, males that had scarce contribution to parental care and males that had provided as much parental care as females. Our results indicate that E. albiceps has a biparental care biased to females, and females can raise a brood without contribution of the male. The great variance in parental care observed among males suggests a monogamous mating system with a low paternity certainty, therefore further studies about the frequency of extra-pair fertilizations will allow us to assess this hypothesis.